Integrated Management and Educational Development - Siabato Patiño, Margarita (Cooperativismo & Desarrollo, 2014)
The aim of this article is to present a summary of the research conducted by the author from 2010 to 2013 in her doctoral thesis, “Contributions to the integrated management of district schools in the city of Bogotá based on an impact evaluation of the Proyecto Educativo Líderes Siglo xxi”, led by uned of Madrid, Spain. The contributions are presented based on the strengths and difficulties encountered in the impact evaluation of schools that participated in the research, the needs that studies have identified in Bogotá’s official education sector, and the author’s thesis experience with ingrated management of official educational institutions. The goal is to contribute to the development of educational institutions through integrated management that is focused on integrated quality of education, talent management, and the creation of an appropriate institutional environment.